Kikuchi necrotizing lymphadenopathy: a tip of the iceberg disease? - Singla, Sushil; Kumar, Mohitesh; Jat, Vinod Kumar; Parwan, Deepika (International Journal of Contemporary Pediatrics, 2021)
Kikuchi-Fujimoto disease (KFD) is a rare benign condition also called histiocytic necrotizing lymphadenitis, which typically presented as fever with cervical lymphadenopathy in previously healthy individual. We presented a case of 11 year old boy with fever and cervical lymphadenopathy since 2 months. Lymph node biopsy was performed which suggested of KFD and was treated symptomatically. KFD incidence is rare but clinicians should be alert if young patient comes with fever and cervical lymphadenopathy to lower the chance of unwanted laboratory test and harmful treatment.